Dynamics of a mechanical frequency up-converted device for wave energy harvesting. (14th April 2016) - Lin, Zheng; Zhang, Yongliang
Abstract: This paper proposes a novel mechanical impact-driven frequency up-converted device for wave energy harvesting, which could bridge a gap between waves of frequency 0.03–1 Hz and electrical generators of operation frequency hundreds hertz. The device mainly consists of a cylindrical buoy, beams and teeth. A mathematical model for the dynamics of such a device is presented, which incorporates the fluid–structure interaction between the wave and the buoy, and the structural interactions between the beams and the teeth. The momentum balance method and the coefficient of restitution are employed, which give rise to piecewise nonlinear equations governing the motions of the buoy and the beams. Experimental tests carried out in a wave flume validate the model and prove the effectiveness of frequency up-converted method in wave energy harvesting. The characteristics of frequency up-converted transformation from buoy motion to beams oscillation for wave energy harvesting are probed, and the effects of beam Young׳s modulus, beam number, wave period and wave height on strain power of the beams are explored.